Abiologic silicon isotope fractionation between aqueous Si and Fe(III)–Si gel in simulated Archean seawater: Implications for Si isotope records in Precambrian sedimentary rocks. (15th August 2016) - Zheng, Xin-Yuan; Beard, Brian L.; Reddy, Thiruchelvi R.; Roden, Eric E.; Johnson, Clark M.
Abstract: Precambrian Si-rich sedimentary rocks, including cherts and banded iron formations (BIFs), record a >7‰ spread in 30 Si/ 28 Si ratios (δ 30 Si values), yet interpretation of this large variability has been hindered by the paucity of data on Si isotope exchange kinetics and equilibrium fractionation factors in systems that are pertinent to Precambrian marine conditions. Using the three-isotope method and an enriched 29 Si tracer, a series of experiments were conducted to constrain Si isotope exchange kinetics and fractionation factors between amorphous Fe(III)–Si gel, a likely precursor to Precambrian jaspers and BIFs, and aqueous Si in artificial Archean seawater under anoxic conditions. Experiments were conducted at room temperature, and in the presence and absence of aqueous Fe(II) (Fe(II)aq ). Results of this study demonstrate that Si solubility is significantly lower for Fe–Si gel than that of amorphous Si, indicating that seawater Si concentrations in the Precambrian may have been lower than previous estimates. The experiments reached ∼70–90% Si isotope exchange after a period of 53–126 days, and the highest extents of exchange were obtained where Fe(II)aq was present, suggesting that Fe(II)–Fe(III) electron-transfer and atom-exchange reactions catalyze Si isotope exchange through breakage of Fe–Si bonds. All experiments except one showed little change in the instantaneous solid–aqueous Si isotope fractionation factor with time, allowing extraction of equilibrium Si isotope fractionation factors through extrapolation to 100% isotope exchange. The equilibrium 30 Si/ 28 Si fractionation between Fe(III)–Si gel and aqueous Si (Δ 30 Sigel–aqueous ) is −2.30 ± 0.25‰ (2 σ ) in the absence of Fe(II)aq . In the case where Fe(II)aq was present, which resulted in addition of ∼10% Fe(II) in the final solid, creating a mixed Fe(II)–Fe(III) Si gel, the equilibrium fractionation between Fe(II)–Fe(III)–Si gel and aqueous Si (Δ 30 Sigel–aqueous ) is −3.23 ± 0.37‰ (2 σ ). Equilibrium Si isotope fractionation for Fe–Si gel systems is significantly larger in magnitude than estimates of a near-zero solid–aqueous fractionation factor between pure Si gel and aqueous Si, indicating a major influence of Fe atoms on Si–O bonds, and hence the isotopic properties, of Fe–Si gel. Larger Si isotope fractionation in the Fe(II)-bearing systems may be caused by incorporation of Fe(II) into the solid structure, which may further weaken Fe–Si bonds and thus change the Si isotope fractionation factor. The relatively large Si isotope fractionation for Fe–Si gel, relative to pure Si gel, provides a new explanation for the observed contrast in δ 30 Si values in the Precambrian BIFs and cherts, as well as an explanation for the relatively negative δ 30 Si values in BIFs, in contrast to previous proposals that the more negative δ 30 Si values in BIFs reflect hydrothermal sources of Si or sorption to Fe oxides/hydroxides.